Candidate pigmentation genes related to feather color variation in an indigenous chicken breed revealed by whole genome data - Wang, Huie; Wen, Junhui; Li, Haiying; Zhu, Tao; Zhao, Xiurong; Zhang, Jinxin; Zhang, Xinye; Tang, Chi; Qu, Lujiang; Gemingguli, M. (Frontiers in Genetics, 2022)
Chicken plumage colour is an inheritable phenotypes which was naturally and artificially selected during domestication. Baicheng You chicken is an Chinese indigenous breed presenting three main feather colors including lavender, blackness and yellowness plumages. In order to explore of genetic mechanisms underlying the pigmentation in Baicheng You chicken breed, we re-sequenced whole genome of Baicheng You chicken with the three plumage colors. By analyzing the diverged genomic regions among the chickens with different feather colors, we identified some candidate genomic regions associated with the feather colors in Baicheng You chickens. We found that EGR1, MLPH, RAB17, SOX5 and GRM5 genes were the potential genes for black feather, lavender feather and yellow feather. MLPH, GRM5 and SOX5 genes have been found to be related to plumage colors in birds. Our results showed that EGR1 is a most plausible candidate gene for black plumage, RAB17, MLPH and SOX5 for lavender plumage, and GRM5 for yellow plumage in Baicheng You chickens.